Digital Transformation of Emergency Management System: Technical Framework and Policy Path - Zhang Weidong; Gao Zhijie; Wang Chaoxian (中国工程科学, 2021)
With the acceleration of the new generation of information technology innovation, the economy and society are showing important new features of digital transformation, and the digital transformation of the emergency management system, which is an important part of the economy and society and the concentrated expression of national governance capabilities, is on the agenda. This article follows the objective laws of technological industry transformation, based on the theoretical paradigm of technical and economic management, tries to portray the characteristics of modern emergency management systems, constructs a technical system and proposes a policy path to promote digital transformation of emergency management systems. Research shows that the current digital transformation technology system and technical capabilities are becoming more and more perfect, and the emergency management system needs digital transformation. It is facing the construction of an emergency management digital transformation technology system covering the three levels of technology, platform and management. It is an important task to promote the balanced development of the physical world and social systems, platform support and management decision-making, technological innovation and integrated applications. To this end, it is recommended that in the process of subsequent emergency management policy design and the formulation of the “14th Five-Year Plan”, it is necessary to strengthen the digital upgrade of emergency management infrastructure, consolidate the foundation of the digital platform for emergency management, and strengthen the integrated application of digital technology in emergency management practices.